(untitled) (Journal of Pharmaceutical Negative Results, 2022)
A study was conducted to study the level of anti-inflammatory (IL-4) and pro-inflammatory (IL-1β, IL-6, IFNγ, TNFα) cytokines in 28 women with physiological pregnancy in the third trimester and in 23 women with incipient labor. It was found that in the prenatal period, the level of IL-1β and IL-8 increases sharply, and the level of IL-4 decreases sharply. The levels of IL-6 and TNFα are also slightly elevated. Therefore, the study of the level of pro- and anti-inflammatory cytokines in parturient women with a physiologically proceeding pregnancy is of great interest, since it is this mechanism of changes in the level of cytokines during incipient labor activity that is observed in a pathologically proceeding pregnancy with the threat of premature birth.